Factors related to the international research collaboration in the health area: A qualitative study - Roya Moradi; Ali Zargham-Boroujeni; Mohammad Reza Soleymani (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: International research collaboration (IRC) is known as one of the important indicators of productivity, efficiency, and validity of universities in the world. In other words, IRC is necessary for the scientific trade-off between researchers in international scientific societies. The study aimed to address the experiences of an academic researcher about factors related to IRC. MATERIALS AND METHODS: The present study was conducted using a qualitative approach and conventional content analysis method. The participants consisted of 19 experienced faculty members and researchers from Isfahan University of Medical Sciences, who were selected based on the purposive and snowball sampling techniques. Data were collected through semi-structured interviews and were analyzed using the content analysis technique. Guba and Lincoln's evaluative criteria, including credibility, confirmability, dependability, and transferability, were applied to evaluate the trustworthiness of the study. RESULTS: According to the research findings, factors of "personal skills," "personality," "professional position," and "scientific activities" under the category of personal factors; "rules and regulations" and "equipment and facilities" under the organizational factors; and "domestic policies" and "foreign policies" were identified under the government factors category. CONCLUSION: Research collaborations are influenced by individual, intra-academic, and extra-academic factors; thus, research policymakers can help further to enhance the quantity and quality of scientific output and promote the university's placing in international rankings through providing conditions that enable international interactions.